Web-Based Human Resource Management System Using Laravel Framework - Vira Deva, Made Marshall; Marini Mandenni, Ni Made Ika; Putra Githa, Dwi (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2025)
This research developed a web-based human resource management system to address manual HR management issues in a financial institution. Manual HR management created challenges including difficult data integration, high risk of recording errors, and inefficient processes. The system was developed using the agile method with MySQL database, Laravel framework, and PHP programming language. This system integrated employee management, performance assessment, payroll, and recruitment modules. Testing was conducted using User Acceptance Testing (UAT) and stress testing method. Research results showed that the system successfully met user needs by optimizing digital and integrated employee data management. The system provided real-time information access, facilitated performance evaluations, and generated comprehensive HR reports. The implementation of this system improved operational efficiency, data accuracy, and decision-making quality through integrated HR management processes.